Patients whose GP knows complementary medicine tend to have lower costs and live longer - Peter Kooreman; Erik W. Baars (Institute for the Study of Labor (IZA), 2011)
Health economists have largely ignored complementary and alternative medicine (CAM) as an area of research, although both clinical experiences and several empirical studies suggest cost-effectiveness of CAM. The objective of this paper is to explore the cost-effectiveness of CAM compared to conventional medicine. A data set from a Dutch health insurer was used containing quarterly information on healthcare costs (care by general practitioner (GP), hospital care, pharmaceutical care, and paramedic care), dates of birth and death, gender and 6-digit postcode of all approximately 150,000 insurees, for the years 2006-2009. Data from 1913 conventional GPs were compared to data from 79 GPs with additional CAM training in acupuncture (25), homeopathy (28) and anthroposophic medicine (26). Patients whose GP has additional CAM training have 0 to 30 percent lower healthcare costs and mortality rates, depending on age groups and type of CAM. The lower costs result from fewer hospital stays and fewer prescription drugs. Since the differences are obtained while controlling for confounders including neighborhood specific fixed effects at a highly detailed level, the lower costs and longer lives are unlikely to be related to differences in socio-economic status. Possible explanations include selection (e.g. people with a low taste for medical interventions might be more likely to choose CAM) and better practices (e.g. less overtreatment, more focus on preventive and curative health promotion) by GPs with knowledge of complementary medicine. More controlled studies (replication studies, research based on more comprehensive data, cost-effectiveness studies on CAM for specific diagnostic categories) are indicated.
urn:nbn:de:101:1-201106202064
Keywords: I11; I12; 330; healthcare costs; life expectancy; complementary medicine